Edukasi Gizi Seimbang Berbasis Pangan Lokal Melalui Demonstrasi Bakso Ikan Sebagai Upaya Peningkatan Pengetahuan Ibu di Desa Barangka Kabupaten Buton - Asdar Asdar; Wa Ode Rizky Azhara; Sri Maladewi; Wa Cimi; Meliawati Samimu; Kartini L (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Stunting remains a major nutritional problem in Indonesia and is closely related to inadequate nutritional intake and low public knowledge regarding balanced nutrition. This community service activity aimed to increase mothers’ knowledge about balanced nutrition and the utilization of local food through a fishball cooking demonstration in Barangka Village, Buton Regency. The activity was carried out on May 2, 2026 involving 12 participants consisting of pregnant women and breastfeeding mothers. The methods used included counseling, educational sessions, cooking demonstrations, and pre-test and post-test evaluations. The educational materials covered stunting prevention, balanced nutrition guidelines, and the processing of local fish into nutritious fishballs. The results showed an increase in participants’ knowledge after the intervention. The proportion of participants with good knowledge increased from 41.67% during the pre-test to 83.33% during the post-test. This activity indicates that balanced nutrition education combined with local food cooking demonstrations can effectively improve community knowledge and awareness regarding stunting prevention.